The Effect of Mass Toothbrushing Demonstration Method Extension on Improving Elementary School Students' Knowledge - Devi Octavia Nugrahani; Nana Novariana; Nova Mega Rukmana (Universitas Ibn Khaldun Bogor, 2026)
Dental and oral health problems remain a major issue among elementary school-aged children, particularly in East Lampung Regency, which has a relatively high prevalence of dental caries. One of the main contributing factors is the low level of children's knowledge regarding proper dental hygiene practices. This study aims to determine the effect of oral and dental health education using a mass toothbrushing demonstration method on improving students’ knowledge at State Elementary School 1 Labuhan Ratu VII. The study employed a pre-experimental design with a one-group pre-test post-test approach. A total of 58 students from grades III and IV were selected using a total sampling technique. The instrument used was a knowledge questionnaire administered before and after the educational intervention, and the data were analyzed using the Wilcoxon test. The results showed a significant increase in knowledge, with a p-value of 0.000 (p < 0.05), where the majority of students shifted from the “low” to “moderate” and “high” knowledge categories.